On the ancient history of Azerbaijani statehood - Nagi, Akif (My University, 2022)
Azerbaijan has a long tradition of statehood. Domestic and foreign historiographies refer to Aratta, Lullubi, Guti, Manna, Media and others as ancient Azerbaijani states. We consider each of these state names as conventional ones. These names given to the ancient Azerbaijani states were not related to the internal, local factors, but appeared as a result of the subjective approach of various sources. This misconception had to be eliminated. The expression “Azerbaijani state” should be used in relation to all states. For instance, expressions such as “Azerbaijani state called Aratta in foreign sources” or “Azerbaijani state ruled by the Lullubi dynasty” should be used. It is incorrect to use terms such as the “state Aratta” or the “Lullubi state”. This erroneous tradition was also used in later periods of our history, or rather, by European and Russian historians, deliberately included in the scientific lexicon in order to falsify the history of Azerbaijan, to put the terms “Azerbaijan” and “Turk” in the background. For instance, the expressions the “Saji state” or the “Safavi state” were made up for this purpose. In fact, the terms “Azerbaijani state during the Saji dynasty” or “Azerbaijani state during the Safavi dynasty” must be used.